Plant Regeneration Through Somatic Embryogenesis From Leaf And Root Explants Of Rhynchostylis Retusa (L.) Blume (Applied Biological Research, 2015)
An efficient protocol for protocorm like bodies (PLBs) was development  and its regeneration through direct somatic embryogenesis was  standardized for Rhynchostylis retusa (L.). Somatic embryos were  developed from leaf and roots and cultured in MS medium  supplemented with different combinations of phytohormones either  individually or in combination. The embryo induction was highest in  leaf (75%) and root (50.2%) when a combination of 1.0 mg L-1 BAP +  1.5 mg L-1 kinetin was used. Germination of somatic embryos was  highest (60%) in ½MS medium with 1.5 mg L-1 BAP. The effect of  different PGRs was observed on multiple shoot induction. Maximum  number (10.20 ± 0.58) and highest length (3.8 cm) of multiple shoots was  observed in MS medium + 1.5 mg L-1 BAP and 1.0 mg L-1 NAA. Highest  number (5.8) and length (4.17 cm) of adventitious roots were seen in ½MS medium + 0.5 mg L-1 IAA and 0.5 mg L-1 IBA. The well rooted  plants were successfully hardened to the pots that contained small brick  pieces, wood charcoal (1:3) and coconut husk; and eventually transferred  to shade house for establishment. Plants showed 60% survival.
Keywords: Rhynchostylis retusa; medicinal orchid; regeneration; PGRs; somatic embryogenesis